Co-Benefits of REDD+ in Community Managed Forests in Nepal (Journal of Forest and Livelihood, 2013)
DOI: http://dx.doi.org/10.3126/jfl.v11i2.8623 Journal of Forestry and Livelihood Vol.11(2) 2013 65-68